Pola Asuh Demokratis, Kemandirian dan Motivasi Berprestasi pada Mahasiswa - David, Lydia Edmay Viveca; Matulessy, Andik; Pratikto, Herlan (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2014)
Abstract. The aim of this research was correlation the democratic parenting style and autonomy toward achievement motivation. The participants are 110 students of Medicine Faculty of Sam Ratulangi University. Instruments research used achievement motivation scale, democratic parenting-style scale and autonomy scale. Cronbach’s Alpha reliability found the reliability of achievement motivation scale α = 0,917 democratic parenting-style scale α = 0,915 autonomy scale α = 0,947 Regression analysis result F = 120,977 and p = 0,000 (p < 0,01) indicated that both of democratic parenting-style and autonomy variables give contributions for the students’ achievement motivation. Partial correlation result between achievement motivation and democratic parenting-style found r partial = 0,031 p = 0,753 (p > 0,05) indicated no correlation between democratic parenting-style and achievement motivation. Partial correlation result between achievement motivation and autonomy found r partial = 0, 775 p = 0,000 ( p < 0,01) indicated that achievement motivation and autonomy was significant positively correlation.Keywords: achievement motivation, democratic parenting-style, autonomy